Effect sizing in the statistical sport data processing - Barnikova, I. E.; Samsonova, A. V.; Tsipin, L. L. (Theory and Practice of Physical Culture, 2019)
Background? Presently one of the key requirements for the international research publications is the effect size calculation, with the effect size considered one of the key verifications of the practical significance of the study findings. International research journals and publishers including those specializing in the physical education and sport matters tend to increasingly reject the study data verified by the p-value only. It is a fairly standard requirement nowadays that a study report shall specify the effect size to confirm the practical benefits of the findings, confidence intervals and effective ranges of the applied criteria[7, 11]. It should be mentioned that the national research publications on the physical education and sport matters seldom if ever give the effect size ratings [9, 14] and give preference in the practical validity ratings to p-values - despite the opinions [5, 12, 10] that the statistical meaning of difference may not always be indicative of the practical significance of such difference.